Conceptual Modeling: Foundations and Applications Essays in Honor of John Mylopoulos - Borgida, Alex T.; Chaudhri, Vinay; Giorgini, Paolo; Yu, Eric.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
This Festschrift volume, published in honor of John Mylopoulos on the occasion of his retirement from the University of Toronto, contains 25 high-quality papers, written by leading scientists in the field of conceptual modeling. The volume has been divided into six sections. The first section focuses on the foundations of conceptual modeling and contains material on ontologies and knowledge representation. The four sections on software and requirements engineering, information systems, information integration, and web and services, represent the chief current application domains of conceptual modeling. Finally, the section on implementations concentrates on projects that build tools to support conceptual modeling. With its in-depth coverage of diverse topics, this book could be a useful companion to a course on conceptual modeling.
John Mylopoulos: Sewing Seeds of Conceptual Modelling -- John Mylopoulos: Sewing Seeds of Conceptual Modelling -- Foundations -- Foundations of Temporal Conceptual Data Models -- Faceted Lightweight Ontologies -- The Ontological Level: Revisiting 30 Years of Knowledge Representation -- Some Notes on Models and Modelling -- A Semantical Account of Progression in the Presence of Defaults -- Social Modeling and i* -- Information Systems -- Data Modeling in Dataspace Support Platforms -- Conceptual Modeling: Past, Present and the Continuum of the Future -- On Conceptual Content Management -- Information Integration -- Conceptual Modeling for Data Integration -- Clio: Schema Mapping Creation and Data Exchange -- Heterogeneity in Model Management: A Meta Modeling Approach -- Associativity and Commutativity in Generic Merge -- Web and Services -- The History of WebML Lessons Learned from 10 Years of Model-Driven Development of Web Applications -- GAMBUSE: A Gap Analysis Methodology for Engineering SOA-Based Applications -- Web Service Composition via the Customization of Golog Programs with User Preferences -- Software and Requirements Engineering -- Dealing with Complexity Using Conceptual Models Based on Tropos -- On Non-Functional Requirements in Software Engineering -- Reasoning About Alternative Requirements Options -- Supporting Requirements Elicitation through Goal/Scenario Coupling -- Enhancing Tropos with Commitments -- Implementations -- (3z(BReducing(3y (BCLASSIC to Practice: Knowledge Representation Theory Meets Reality -- The KBMS Project and Beyond -- Using the ConGolog and CASL Formal Agent Specification Languages for the Analysis, Verification, and Simulation of i* Models.s
Keywords: Application software; Software engineering; Computers; Data mining; Programming languages (Electronic computers).; Information Systems Applications (incl. Internet).; Software Engineering; Information Systems and Communication Service; Data Mining and Knowledge Discovery; Software Engineering/Programming and Operating Systems; Programming Languages, Compilers, Interpreters